2020
DOI: 10.1101/2020.03.10.984906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional repression of Myc underlies AGO1’s tumour suppressor function

Abstract: Here we report novel tumour suppressor activity for the Drosophila Argonaute family RNA binding protein AGO1, a component of the miRNA-dependent RNA-induced silencing complex (RISC). The mechanism for growth inhibition does not, however, involve canonical roles as part of the RISC; rather AGO1 controls cell and tissue growth by functioning as a direct transcriptional repressor of the master regulator of growth, Myc. AGO1 depletion in wing imaginal discs drives a significant increase in ribosome biogenesis, nuc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(68 reference statements)
1
0
0
Order By: Relevance
“…5 D ). In line with reports highlighting small RNA–independent nuclear roles of AGO proteins in D. melanogaster ( Zaytseva et al, 2020 Preprint ), the evidence reported here points us to a positive role of AGO1 in E2-regulated gene expression that does not depend on small RNA binding and small RNA­–RNA interactions.…”
Section: Resultssupporting
confidence: 92%
“…5 D ). In line with reports highlighting small RNA–independent nuclear roles of AGO proteins in D. melanogaster ( Zaytseva et al, 2020 Preprint ), the evidence reported here points us to a positive role of AGO1 in E2-regulated gene expression that does not depend on small RNA binding and small RNA­–RNA interactions.…”
Section: Resultssupporting
confidence: 92%